2018
DOI: 10.1248/bpb.b18-00185
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cellular Transport and Binding Processes of Unesterified Docosahexaenoic Acid in Outer Blood–Retinal Barrier Retinal Pigment Epithelial Cells

Abstract: Docosahexaenoic acid (DHA, 22 : 6) is an essential omega-3 long-chain polyunsaturated fatty acid that plays a pivotal role in vision. The purpose of this study was to clarify the cellular uptake and binding processes of free and protein-bound unesterified DHA in retinal pigment epithelial cell (RPE) line ARPE-19 as a model of the human outer blood-retinal barrier and isolated porcine RPE cell fractions. Uptake of free [C]DHA by ARPE-19 cells was saturable with a Michaelis-Menten constant of 283 µM, and was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Unlike the brain which acquires DHA predominantly through the Mfsd2a pathway, retina appears to acquire DHA through multiple pathways, since a deficiency of Mfs2a results in only a 45% reduction in retinal DHA, and a 57% reduction in VLCFA [ 47 ]. Thus, the studies by Bazan [ 18 ] showed the importance of Adiponectin receptor for maintaining the DHA levels of retina, whereas the role of FA-binding proteins and lipoprotein receptors have been proposed by others [ 3 , 19 ]. These pathways may account for the small increase in retinal DHA by dietary free DHA and TAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the brain which acquires DHA predominantly through the Mfsd2a pathway, retina appears to acquire DHA through multiple pathways, since a deficiency of Mfs2a results in only a 45% reduction in retinal DHA, and a 57% reduction in VLCFA [ 47 ]. Thus, the studies by Bazan [ 18 ] showed the importance of Adiponectin receptor for maintaining the DHA levels of retina, whereas the role of FA-binding proteins and lipoprotein receptors have been proposed by others [ 3 , 19 ]. These pathways may account for the small increase in retinal DHA by dietary free DHA and TAG.…”
Section: Discussionmentioning
confidence: 99%
“…This is because they are all absorbed predominantly in the form of triacylglycerol (TAG) [ 15 , 16 ], whereas enrichment of brain and retina requires a phospholipid form of DHA [ 17 ]. Although previous studies have shown that the uptake of DHA by retina involves lipoprotein receptors [ 3 ], adiponectin receptor [ 18 ], and multiple fatty acid transporters [ 19 ], more recent studies suggest that the predominant pathway for DHA uptake by retina may be through the Mfsd2a (major facilitator superfamily domain-containing protein 2a) pathway [ 20 ]. Since the DHA from the currently used supplements is absorbed mostly as TAG, whereas the Mfsd2a pathway requires a lysophospholipid form of DHA [ 17 ], it is possible that retinal DHA was not appreciably enriched by these supplements.…”
Section: Introductionmentioning
confidence: 99%
“…RPE expresses factors required for lipoprotein intake, cholesterol and lipoprotein synthesis and secretion, as well as reverse cholesterol transport (RCT) [94]. Phagocytosis and degradation of the POSs are the principal lipid source for the RPE [95], as well as processing and recycling back to the photoreceptors of vitamin A and of DHA [96,97]. Moreover, excess cholesterol is loaded on HDLs by ABC transporters and, then, removed, or it is also secreted in VLDL-like lipoproteins basolaterally into Bruch's membrane where it forms drusen [98].…”
Section: Discussionmentioning
confidence: 99%
“…For example, DHA, an essential omega-3 long-chain polyunsaturated fatty acid, is known to have anti-inflammatory properties on glial cells and influences memory and cognitive functions (28). After its transport in blood via the lipocalin retinol-binding protein 4 (RBP4), LDL lipoparticles, or serum albumin (29), it crosses the cell membrane and travels across the brain endothelial cell cytoplasm via FABP5 (30). Lipocalins and FABPs manage lipids not only across the BBB but also between cells in the nervous system (glia-to-glia or glia-to-neuron).…”
Section: Lipids and Their Protein Managers Are Involved In Key Procesmentioning
confidence: 99%